2021
DOI: 10.1038/s41586-021-03925-1
|View full text |Cite
|
Sign up to set email alerts
|

Lectins enhance SARS-CoV-2 infection and influence neutralizing antibodies

Abstract: This is a PDF file of a peer-reviewed paper that has been accepted for publication. Although unedited, the content has been subjected to preliminary formatting. Nature is providing this early version of the typeset paper as a service to our authors and readers. The text and figures will undergo copyediting and a proof review before the paper is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers apply.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
319
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 282 publications
(344 citation statements)
references
References 69 publications
24
319
0
1
Order By: Relevance
“…S2K146 induced shedding of the S1 subunit as efficiently as the RBM-targeting S2E12 mAb, whereas the control mAb S2M11 did not as it locks S in the prefusion closed state (13) (Fig 4C). Furthermore, we found that the S2K146 Fab triggered the fusogenic rearrangement of a wildtype-like S ectodomain trimer, as we previously described for several SARS-CoV and SARS-CoV-2 neutralizing mAbs (14,(31)(32)(33) (Fig 4D). These data show that S2K146-mediated sarbecovirus neutralization relies on competitively blocking viral attachment to the ACE2 receptor and inactivation of S trimers at the surface of virions before encountering host cells.…”
Section: S2k146 Inhibits Ace2 Engagement and Protects Hamsters From Sars-cov-2 Challengesupporting
confidence: 84%
See 1 more Smart Citation
“…S2K146 induced shedding of the S1 subunit as efficiently as the RBM-targeting S2E12 mAb, whereas the control mAb S2M11 did not as it locks S in the prefusion closed state (13) (Fig 4C). Furthermore, we found that the S2K146 Fab triggered the fusogenic rearrangement of a wildtype-like S ectodomain trimer, as we previously described for several SARS-CoV and SARS-CoV-2 neutralizing mAbs (14,(31)(32)(33) (Fig 4D). These data show that S2K146-mediated sarbecovirus neutralization relies on competitively blocking viral attachment to the ACE2 receptor and inactivation of S trimers at the surface of virions before encountering host cells.…”
Section: S2k146 Inhibits Ace2 Engagement and Protects Hamsters From Sars-cov-2 Challengesupporting
confidence: 84%
“…The SARS-CoV-2 S 'wildtype' ectodomain trimer used for refolding experiments followed by negative stain EM was engineered as follows and recombinantly expressed as previously described (32). The SARS-CoV-2 S D614G 'wildtype' has a muphosphatase signal peptide ending in ETGT, begins at Q14, a mutated S1/S2 cleavage site (SGAR), ends at residue K1211 and is followed by a TEV cleavage site, fold-on trimerization motif, and an 8× His tag in the pCMV vector.…”
Section: Recombinant Protein Productionmentioning
confidence: 99%
“…Our deep mutational scanning measured binding to yeast-displayed RBD, which may not capture all relevant features of full-length spike in the context of virus. Finally, our neutralization assays used pseudotyped lentiviral particles and ACE2-overexpressing cells, and some recent works suggest that the relative importance of different spike epitopes for neutralization can depend on the viral system and target cell line used (7,35,36,60).…”
Section: Discussionmentioning
confidence: 99%
“…2C). One caveat is that all neutralization assays were performed in 293T cells overexpressing ACE2, which tend to emphasize the effect of RBD-binding, ACE2-competitive antibodies more than assays performed on cells with lower levels of ACE2 expression (7,35,36).…”
Section: Infection With B1351 Elicits a Neutralizing Antibody Response At Least As Rbd-focused As Early 2020 Virusesmentioning
confidence: 99%
“…Interestingly, cholesterol-bound RNA probes are targeted to mitochondria 60 . Furthermore, several alternative entry factors to ACE2 and facilitators capable to mediate SARS-CoV-2 infection have been identified [61][62][63][64] , and they could mediate SARS-CoV-2 caveolae-mediated endocytosis. Taken together, it is possible that the diversity of receptors and entry pathways exploited by SARS-CoV-2, together with the fast dynamics of PM-mitochondria communication can obscure the caveolae role.…”
Section: Mitochondria Infection By Vrnamentioning
confidence: 99%